Fragility analysis of high CFRDs subjected to mainshock-aftershock sequences based on plastic failure. (1st March 2020) - Pang, Rui; Xu, Bin; Zhou, Yang; Zhang, Xu; Wang, Xingliang
Highlights: Fragility of high CFRDs considering mainshock-aftershock sequences is investigated. All materials of the CFRD are simulated using elastoplastic models. EDP which can best reflect cumulative damage effect of aftershocks is selected. The effects of aftershock on the fragility of CFRDs are discussed from two aspects. Abstract: Numerous earthquake disasters have demonstrated that secondary damage to structures induced by aftershocks may seriously threaten the seismic safety of structures since the mainshock may have already weakened structural integrity. This paper investigates the fragility of a 200-m high concrete face rockfill dam (CFRD) subjected to mainshock-aftershock sequences based on multiple stripes analysis (MSA). A modified generalized plasticity model and a plastic-damage model are used to describe the nonlinearity of the rockfills and the concrete face slabs, respectively. A series of nonlinear dynamic time history analyses for the CFRD under mainshock-aftershock sequences with different intensity combinations are conducted. The analysis focuses on the deformations, the shear strains and the damage index (DI) of the face slabs. According to the analysis results, the vertical deformation is the best indicator of the cumulative damage inflicted by aftershocks on the high CFRD. Then, considering the importance of face slab damage to the integrity and performance of the CFRD, the influences of aftershocks on the probability of the CFRD reaching a specific limit state are discussed based on vertical deformation and DI. The results reveal that aftershocks can significantly increase the fragility of the CFRD when it has been damaged by mainshocks.